Floristic and Soil Characteristic at The RPH Sentul-Probolinggo Protected Low Land Forest, East Java - Abban Putri Fiqa; Agung Sri Darmayanti (Universitas Gadjah Mada, 2018)
East Java’s forest has a less ideal area based on predetermined requirements. Therefore, rehabilitation was done to meet these requirements and to improve the quality of existing forests. This research was conducted to identify the character of protected forest in Resort Pemangku Hutan (RPH) Sentul area, about vegetation structure and abiotic factor of lowland forest area with low rainfall. The research was conducted by explorative method with plot making for tree plant, sapling and ground cover to inventory and determine the forest vegetation structure inside the area, also by measuring the environmental parameters (temperature, humidity and light intensity) and making soil sampling to analyze biophysical condition. Data were analyzed descriptively both on vegetation condition and physical condition of land and its environment. The result showed that there were identified 84 species from 39 plant families either as trees, sapling or ground cover, with species of Moraceae as the largest contributor. The diversity index of the three types of vegetation shows a medium categorized, while the index of evenness indicates a good categorized that is close to one. Based on the existence of exotic species, especially on ground cover, within protected forest areas, this area has been degraded although not large. However, the physical condition of the soil and environmental conditions in the forest still indicate that this area is still quite good when used as a reference area on rehabilitation program with similar geographical conditions.Keywords: vegetation structure, soil characteristic, low land forest, RPH Sentul Probolinggo